Pengaruh Work-life Balance Terhadap Kepuasan Kerja Karyawan Pada Hotel Sintesa Peninsula Manado - Fenia A. Rondonuwu; Wehelmina Rumawas; Sandra Asaloei (JURNAL ADMINISTRASI BISNIS, 2018)
Human resource is the resource that plays an important role in order to achieve company goals. Human resource management that will positively impact for good. Manado has a growth rate and competition as well as the culture, the style changes work, work culture, family needs, job demands, quickly taking place which eventually increase the population of the breadwinner of the family and responsibility, so between working life and family life in the sometimes arises friction or pressure. It resulted in a lack of a sense of belonging and more willingness to maximize the performance that comes from self-employee against the company. Sintesa Peninsula Hotel is one of the five star hotels in Manado that have so many employees. Therefore, everyone should be able to balance between work and personal as well. This research was conducted to find out whether the work-life balance can affect job satisfaction of the employees at the Hotel Sintesa Peninsula Manado. Work-life Balance as a free variable consists of three balance balance balance of time, namely engagement and satisfaction of the balance. As for job satisfaction as a bound variable is divided into five dimensions of job satisfaction that is the work itself, salaries, promotional opportunities, supervision and co-workers. This type of research using quantitative research using survey method. The data used in this study is a questionnaire distributed to 60 respondents. Methods of data analysis used is a simple linear regression. To analyze the data using SPSS program assisted. The results of this research suggest that work-life balance has an impact on employee job satisfaction on Hotel Synthesis Peninsula Manado of 37.4% while 63.6% are affected by other variables not examined in this study.